Perbandingan Persepsi Kualitas Pelayanan dan Kepuasan Konsumen Online Food Delivery - Ika Purwanti; Sawabi; Risky Dharmawan (Bulletin of Management and Business, 2023)
This study aims to determine the comparison of service quality perceptions and consumer satisfaction of national online food delivery services (Grab Food) and local food delivery (Cak Ed Food), with a case study of Grab Food and Cak Ed Food consumers in Lamongan. The research approach used is quantitative-comparative. The population in the study were people who had used Grab Food and Cak Ed Food services, while the research sample was 100 respondents. The data was analysed using the paired sample T-Test test with the help of the SPSS application. The results showed that there was no significant difference between Grab Food service quality and Cak Ed Food service quality, and there was a significant difference between Grab Food customer satisfaction and Cak Ed Food customer satisfaction.